Oral and Systemic Health in Older Adults: The Imperative Role of Nurses and Dentists in Integrated Smoking Cessation Programs - Alsulami, Musab Abdullah; Oraybi, Ahmed Taher Shui; Alharbi, Abeer Ahmad; ALQASIMI , SAUD NAHI; Alnakle, Roqaih Hussain; SHAREEF, OTHMAN MOHAMMED; Al-Otaibi, Khaled Saad Misfer; Al-Balawi, Nora Mohammed Najih; Habtar , Ameera Saeed; Sofyani, Heyala Yahya; Alanzi, Abdullah Munadi; Alqahtani , Mathkar Eid; et al. (Journal of Ecohumanism, 2024)
Background: Oral health is a critical component of overall health, particularly in older adults who face increased risks of oral and systemic diseases. Despite the preventability of many oral disorders, significant disparities exist, exacerbated by factors such as age, socioeconomic status, and access to care. Smoking and other lifestyle choices further complicate these health challenges. Methods: This review synthesizes current literature on the integration of oral health into general healthcare systems for elderly populations. A comprehensive analysis of studies from databases such as PubMed and Google Scholar was conducted, focusing on the roles of dental and nursing professionals in smoking cessation programs and their impact on oral and systemic health. Results: Findings indicate that incorporating oral health into general healthcare services significantly improves health outcomes for older adults. Dental practitioners are essential in advocating for smoking cessation, which can mitigate risks of periodontal disease and other systemic conditions. The review highlights various strategies for integration, including multidisciplinary cooperation, patient education, and addressing common risk factors. Conclusion: The integration of oral health into overall healthcare is vital for enhancing the health of older individuals. By addressing shared risk factors and fostering collaboration among healthcare providers, it is possible to reduce the prevalence of oral disorders and improve quality of life. Policymakers and health organizations must prioritize these strategies to ensure effective healthcare delivery for aging populations